Integrated systems research in nutrition-sensitive landscapes: A theoretical methodological framework - Groot, Jeroen C.J.; Kennedy, G.; Remans, R.; Estrada-Carmona, Natalia; Raneri, Jessica Evelyn; DeClerck, Fabrice A.J.; Álvarez, S.; Mashingaidze, N.; Timler, Carl J.; Stadler, M.; Rio Mena, T. del; Horlings, L.; et al. (Routledge, 2017)
Integrated systems research is one of the pillars in the nutrition-sensitive landscapes (NSL) approach that is being implemented in case-study sites in Zambia and Kenya. This chapter describes systems and systematically explores windows of opportunity for sustainable redesign and innovation in landscape and farm systems for improved nutrition using whole-farm and landscape models for each site. It discusses the strengths and challenges of systems approaches in agricultural research based on interactions with smallholder communities from the three diverse settings. The NSL approach investigates how improved land-use and management of resources in farms and landscapes can improve the livelihoods of rural people, their nutritional status and the ecosystem services that landscapes provide. To address and include the culture, values and priorities of people in nutrition-sensitive landscapes during the investigation and support of the envisioned development pathways, an inclusive approach to learning cycles is used.